The importance of folate consumption during pregnancy in preventing neural tube defects: A Literature Review - Tiara Andhiny; Anita Rahmiwati; Novrikasari Novrikasari (Poltekkes Kemenkes Aceh, 2026)
Background: Neural Tube Defects (NTDs) are severe congenital disorders that can result in lifelong disabilities. These malformations are largely preventable through adequate folic acid intake before conception and during early pregnancy. However, in many settings, including Indonesia, pregnant women’s awareness and adherence to folic acid supplementation remain below optimal levels. Scientific evidence has long demonstrated that folic acid supports proper neural tube formation and lowers the risk of conditions such as spina bifida and anencephaly. However, there is limited discussion in existing reviews about contextual barriers, such as cultural perceptions, healthcare access, and policy limitations, that influence supplementation practices in low- and middle-income countries. This review aims to fill this gap by examining recent evidence on the preventive role of folic acid and exploring the factors that shape its effectiveness.Objectives: This study aimed to evaluate and review the existing evidence on the role of folic acid consumption in preventing Neural Tube Defects (NTD) in pregnant women and to identify factors that influence its effectiveness.Methods: This review was conducted using PubMed and Google Scholar with searches guided by standardized Medical Subject Headings (MeSH) terms: “Folic Acid,” “Pregnant Women,” and “Neural Tube Defects.” The selection process followed the PRISMA guidelines, applying the following criteria: publication between 2020 and 2024, availability of full-text articles, and a primary focus on the relationship between folic acid and NTD prevention in pregnant women. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool.Results: The results of the six studies showed that folic acid deficiency significantly increased the risk of anencephaly and neural tube defects, whereas folic acid supplementation before and during pregnancy reduced the incidence of NTDs. Adequate folic acid levels in pregnant women also reduce the risk of spina bifida, although knowledge and compliance with folic acid consumption among pregnant women remain low. The methodological quality varied from moderate to high, although several studies did not adequately control for confounding factors.Conclusion: Based on these findings, folic acid consumption is crucial for preventing NTDs. However, there is a need to improve education and compliance with folic acid consumption among pregnant women. Further research is required to understand the factors influencing compliance and to design more effective interventions to enhance awareness and implementation of folic acid consumption among pregnant women.